2014
DOI: 10.1007/s00296-014-3099-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in widespread pain: its effect on pain perception, quality of life and nerve conduction studies

Abstract: The aim of the study was to investigate the effects of hypovitaminosis D on pain, quality of life (QoL) and nerve conduction studies (NCSs) in patients with chronic widespread pain (CWP). We randomly selected 83 female patients with CWP according to their vitamin D levels in this cross-sectional study. Patients were divided into two groups as sufficient vitamin D level (above 20 ng/ml) and deficient vitamin D level (below 20 ng/ml, hypovitaminosis D). Various pain scales and Nottingham Health Profile (NHP) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
0
21
2
1
Order By: Relevance
“…So far, to our knowledge, no one has investigated the VDBP levels in plasma from CWP patients. However, it is more common to analyze vitamin D metabolites, and several studies have found decreased levels in chronic low back pain53 and FMS/CWP patients 54,55. This is in conflict with our result, showing increased levels of both vitamin D and VDBP.…”
Section: Discussioncontrasting
confidence: 99%
“…So far, to our knowledge, no one has investigated the VDBP levels in plasma from CWP patients. However, it is more common to analyze vitamin D metabolites, and several studies have found decreased levels in chronic low back pain53 and FMS/CWP patients 54,55. This is in conflict with our result, showing increased levels of both vitamin D and VDBP.…”
Section: Discussioncontrasting
confidence: 99%
“…There was no association found between vitamin D status and sleep, or any quality‐of‐life domains on the NHP and SF‐36. This is contradictory to previous research in premenopausal women, and women with chronic pain (unlike current study where 74·8% were male), where vitamin D deficiency is associated with worse SF‐36 and NHP quality‐of‐life scores, particularly in vitality, physical and mental component subscores . However, there are many factors that may affect quality of life, in addition to mood and cognitive function.…”
Section: Discussioncontrasting
confidence: 99%
“…Although rarely considered in rehabilitation clinics, vitamin D deficiency should be accounted for in the differential diagnosis of pain, as it has been reported to be an important factor . Previous studies suggest that vitamin D plays a role in the etiology of fibromyalgia, and non‐specific musculoskeletal pain and vitamin D deficiency have been identified in these patients .…”
Section: Discussionmentioning
confidence: 99%